UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SDN 11 MANDAU PADA MATERI IPS MENGGUNAKAN METODE MAKE A MATCH BERBANTUKAN MEDIA GAMBAR - Zulrahmiati Yuda (JURNAL MANAJEMEN PENDIDIKAN, 2022)
One way that can be used to improve the quality of the process and learning outcomes is to apply the make a match method with the aid of image media. Improvements in learning need to be done so that student learning outcomes in knowledge competence are above the KKM. The purpose of this study was to determine the increase in student learning outcomes after the application of the make a match method with the aid of image media. This type of research is classroom action research. This research was carried out in two cycles and was carried out in the odd semester of the 2021/2022 Academic Year. The subjects of this study were students of class VI SDN 11 Mandau, totaling 30 students. The results showed that the make a match method could improve student learning outcomes. This is evidenced by the increase in the percentage of students who score above the minimum score criteria. In the pre-cycle there were 17 students (56.67%) who scored above the minimum score criteria and 13 students (43.33%) were still below the minimum score criteria. In the first cycle there were 22 students (73.33%) whose scores were above the minimum score criteria, there was an increase of 16.67% while 8 students (26.67%) were below the minimum score criteria. In cycle II, the number of students who got scores above the minimum score criteria was 80% and only 20% had their learning outcomes below the minimum score criteria.